Two-Hour Postprandial Lipoprotein Particle Concentration Differs Between Lean and Obese Individuals - Parvaresh Rizi, Ehsan; Baig, Sonia; Loh, Tze Ping; Toh, Sue-Anne; Khoo, Chin Meng; Tai, E. Shyong (Frontiers in Physiology, 2019)
There is an association between certain lipoprotein particle concentration and risk of cardiovascular diseases, which has mostly established in fasting state. It is unclear whether such detrimental postprandial lipoproteinemia can be revealed as early as 2 hours following a meal challenge in subjects with obesity. In this study we aimed to assess whether various meal compositions can reveal adverse short-term (2-hours) postprandial lipoproteinemia in obese insulin resistant (obese-IR) subjects as compared to lean insulin sensitive (lean-IS) subjects. In a randomized cross-over trial, 9 lean-IS and 9 obese-IR Chinese men aged 22-35 years were challenged with isoenergetic and isovolumic meals rich in protein (HP), fat (HF), or carbohydrate (HC). Plasma samples were collected after a 10 hour fast, as well as 1-h and 2-h post meal and analyzed using nuclear magnetic resonance. Plasma concentration of large very low density lipoproteins (VLDL) and chylomicrons particle was higher and increased more after all meals in obese-IR compared to lean-IS subjects. The HP meal decreased small low density lipoprotein (LDL) particle concentration in obese-IR subjects, and increased small high density lipoprotein (HDL) particle concentration in all subjects. The HF meal led to a decrease in small HDL concentration in all subjects. In conclusion, obese-IR subjects revealed a detrimental response to meal challenges even as early as 2 hours after meal intake.